Personalized Nutrition Recommendations Improve Plasma Metabolite Concentrations Related to Dietary Intake. (29th May 2020) - Schroder, Theresa; Wang, Windy; Cochrane, Kelsey; Vayali, Thara; Cottle, Andrew; Goh, Grace; Marcu, Ana; Parikh, Devansh; Tsoi, Eric; Wishart, David; Anwar, Mohammad; Fraser, Rob
Abstract: Objectives: The objectives of our proof-of-concept study was to assess the efficacy of personalized nutrition interventions on diet and chronic disease risk. Methods: Fasting plasma samples were collected at day 1 and day 100 of a cohort of 148 adults (aged 23–65y) volunteers with a median (range) BMI of 25.8 (17.2–48.3). At both time points 119 metabolites were quantitated using LC-MS/MS. Based on their metabolite concentrations and dietary preferences, each participant received their own personalized nutrition recommendations through an AI-assisted online platform and were advised to follow the recommendations for 100 days. Plasma metabolite concentrations from Day 1 and Day 100 were compared using a paired t-test with Holm-Bonferroni correction ( P  < 0.05). Results: After 100 days, statistically significant changes in acylcarnitine, phosphatidylcholine and amino acid concentrations indicated participants had increased their intakes of omega-3 fats and whole grains and decreased their intakes of saturated fat. For example, Betaine, a biomarker of whole grain intake, increased significantly in concentration from Day 1 to Day 100 [mean (SD): 34.3 (13.2) to 45.3 (15.6) umol/l]. Overall, 55 of the analyzed 119 metabolites' (46%) concentrations had previously been linked to dietary intake according to a systematic literature search that was used to generate evidence-based personalized nutrition recommendations. Concentrations of 33 (60%) of these 55 metabolites changed significantly. The majority [26 (79%)] of the metabolite concentrations changed in a predicted manner consistent with the literature, particularly those metabolites associated to chronic disease risk. For example, a significant decrease in asymmetric dimethylarginine concentration [mean (SD): 0.54 (0.15) to 0.48 (0.12) umol/L] which is understood to result in a decreased cardiovascular disease risk. Conclusions: Adherence with an evidence-based personalized nutrition plan based on a panel of serum metabolomic data can significantly modify serum metabolite concentrations in a direction that can reduce the risk of chronic disease. Further analysis in how these changes relate to chronic disease risk is warranted. Funding Sources: This study was supported by Mitacs and Molecular You.